Optimizing Residential Energy Systems in Households: A Model Integrating Energy Assets with Economic Evaluation through LCOCE - Tadesse, Yeabsira Yetagessu; Erenoglu, Aye Kubra; Sancar, Semanur; Erdinc, Ozan (IEEE, 2024)
In response to the growing need for sustainable and cost-effective residential energy solutions, This paper presents an optimization model aimed to effectively manage the integration of photovoltaic (PV) panel, electric vehicle (EV), residential battery energy storage system (BESS), and hybrid heat pumps. Utilizing dynamic tariffs, the model optimizes energy consumption and generation, focusing on economic analysis through the Levelized Cost of Consumed Energy (LCOCE). The study evaluates the possibility of these integrations to improve energy efficiency and reduce costs, with LCOCE providing a critical metric for economic viability. The results reveal that dynamic-rate tariffs and optimized energy management strategies significantly reduce household electricity bills compared to fixed-rate tariffs. For instance, the optimized model achieved up to a 70.34% reduction in annual electricity bills compared to the base case. Furthermore, the model consistently demonstrated positive return on investment (RoI) for PV and heat pump systems, with PV achieving RoI values up to 2.78 and heat pumps reaching 1.09. In contrast, BESS showed negative RoI due to high initial and replacement costs. Additionally, the LCOCE analysis highlights the substantial savings and potential revenue generation from energy sold back to the grid. This underscores the economic and operational benefits of optimized energy management strategies, paving the way for informed decisions in adopting renewable energy technologies for households.
Keywords: Home Energy Management; Levelized Cost of Consumed Energy (LCOCE); Renewable Energy Integration; Optimization Model; Energy Efficiency; Energy Assets; Sustainable Energy Solutions; MANAGEMENT; Energy & Fuels; Engineering